EFFECTS OF EXCHANGE RATE VOLATILITY ON BRAZILIAN ECONOMIC GROWTH - Pianca, Osmar José Bertholini; Teixeira, Arilton; Cruz, Poliano Bastos da (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
This study aims to capture accurately the effect of volatility of the exchange rate on growth. Following the literature, the analysis was performed in a developing country, intending to identify the direct effect of volatility on growth. Unlike the majority of prior empirical research, it was performed an analysis in a single country aiming to mitigate data comparability issues. We chose to Brazil because it is the country most notably among the BRICs, according to the OECD, and a research suggests that historical series correlated with growth have similar behavior to that observed in the world. Volatility was measured by eight distinct metrics and growth was measured by two metrics. The regressions were estimated by the Generalized Method of Moments, due to its better properties of small samples and to address endogeneity issues. The results of this study suggest that exchange rate volatility negatively affects growth.